Characterization of Alginate with Natural Polymers Combination for Drug Encapsulation - Annisa, Viviane; Sulaiman, Teuku Nanda Saifullah; Nugroho, Akhmad Kharis; Nugroho, Agung Endro; Roman Kutsyk (Iraqi Journal of Pharmaceutical Sciences, 2022)
Alginate is one of the natural biopolymers that is widely used for drug formulations, combination of alginate with other polymers, such as gum acacia, pectin, and carrageenan can increase mechanical strength, therefore, can reduce leakage of the encapsulated active pharmaceutical ingredient from the polymer matrix. Interaction of alginate and these polymers can occur via intermolecular hydrogen bonds causing synergism, which is determined from the viscosity of polymer mixture. Alginate was combined with gum acacia/pectin/carrageenan in different blending ratios (100:0, 75:25, 50:50, 25:75, and 0:100) with and without addition of CaCl2. The synergism effect is obtained from the design of experimental (DoE), and calculation the percentage value of viscosity deviation viscosity synergism index, then the strength of gel was analyzed. The interaction between two polymers was observed using FTIR spectroscopy. In distilled water, the synergistic effect was found in the combination of alginate-carrageenan at ratios 25:75 and 50:50. Otherwise, in CaCl2 solution, synergistic effect appears in alginate-gum acacia (75:25), alginate-pectin (50:50 and 75:25), and alginate-carrageenan (50:50 and 75:25). The synergistic effect and strength of gel polymers increased, with the addition of CaCl2.